COVID-19 and its prevention in internally displaced person (IDP) camps in Somalia: impact on livelihood, food security and mental health - Mumin, F.I.; Wesonga, F.D.; Handuleh, J.I.M.; White, R.G.; Mor, Siobhan M. (Springer, 2022)
Background Somalia has over 2.6 million internally displaced people (IDP) that depend on daily wages and humanitarian assistance for their livelihoods. This study investigated the impact of COVID-19 on livelihoods, food security and mental health of Somalia’s IDPs.